2009
DOI: 10.4000/remi.4988
|View full text |Cite
|
Sign up to set email alerts
|

Anthropologie et migrations africaines en France : une généalogie des recherches

Abstract: Longtemps la perception et le traitement de l'immigration en France ont rimé avec Maghreb. La présence en France de ressortissants des pays d'Afrique subsaharienne, plus tardive il est vrai, et moins importante numériquement que celle des populations d'Afrique du Nord est longtemps passée inaperçue. Par ailleurs, s'agissant de la constitution du champ scientiique, si les thématiques relatives aux migrations sont restées des années durant largement marginalisées voire dépréciées, des disciplines telles la géogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…From the early 1960s until the early 1980s, West African migrations, particularly from the region of the Senegal River, were analysed mainly from the perspective of a Marxist paradigm. The migrant – who was essentially seen as an immigrant – was often considered illiterate, someone coming from a rural area who was exploited for his labour power (Kuczynski and Razy 2009: 82). In the 1990s, following research in other areas, notably Alain Tarrius's (1992) work on Marseille and the Maghreb, studies of migration tended to focus less on immigration and the place of immigrants in the host society – questions formulated in French public debate under the term ‘integration’ – and more on phenomena of circulation (Tarrius 1992).…”
Section: Different Migratory Imaginaires In Senegalmentioning
confidence: 99%
See 1 more Smart Citation
“…From the early 1960s until the early 1980s, West African migrations, particularly from the region of the Senegal River, were analysed mainly from the perspective of a Marxist paradigm. The migrant – who was essentially seen as an immigrant – was often considered illiterate, someone coming from a rural area who was exploited for his labour power (Kuczynski and Razy 2009: 82). In the 1990s, following research in other areas, notably Alain Tarrius's (1992) work on Marseille and the Maghreb, studies of migration tended to focus less on immigration and the place of immigrants in the host society – questions formulated in French public debate under the term ‘integration’ – and more on phenomena of circulation (Tarrius 1992).…”
Section: Different Migratory Imaginaires In Senegalmentioning
confidence: 99%
“…In the case of sub-Saharan African nationals, some studies underlined these dynamics in connection with the Congolese diaspora in Paris. The studies by Didier Gandoulou (1989) on the phenomenon of ‘clothing’ or ‘gear’ ( la sape ) have shown that the migration experience was not necessarily linked to economic distress but ‘conceived as an initiatory journey; it allowed them [migrants] to turn designer clothes into material and symbolic capital’ (Kuczynski and Razy 2009: 94). Nevertheless, it should be noted that, in the Senegalese case, networks of Sufi orders were at the centre of any analysis.…”
Section: Different Migratory Imaginaires In Senegalmentioning
confidence: 99%
“…Fue sólo a partir de la década de los años sesenta "cuando su presencia en Francia comenzó a ser más intensa, que los inmigrantes africanos hicieron su aparición en algunos pocos y raros estudios en ciencias sociales" 3 (Kuczynski & Razy, 2010). Así, aunque es posible encontrar investigaciones francesas en relación con África o con las poblaciones negras de los departamentos y territorios de ultramar (DOMTOM 4 ), para estos estudios la condición negra no ha sido un eje de investigación en sí mismo, sino una variable a controlar, una condición demográfica a tener en cuenta, sin constituir de ninguna manera un eje temático de investigación.…”
Section: La Condición Negra En Franciaunclassified
“…In the 1980s, the State took possession of this debate in response to a growing demand for knowledge about the immigrant population and living conditions in France, coming from social workers, employees of the education and health systems, and administrative personnel (Kuczynski & Razy 2009). It issued calls for project proposals, mostly through State structures such as FAS, 4 DPM 5 and CNDP, 6 and through community organizations, many of which were funded by the aforementioned entities.…”
Section: When Migrants Arrive and Religion Followsmentioning
confidence: 99%